The Effect of Different Size Recirculation Systems on the Quality of Water in Tilapia (Oreochromis niloticus) Culture - Firmansyah, Wahyu; Cokrowati, Nunik; Scabra, Andre Rachmat (Jurnal Perikanan dan Kelautan, 2021)
This study aims to analyze the effect of different cross-sectional areas of recirculation systems on water quality in tilapia (Oreochromis niloticus) rearing. The method used is an experimental method with a completely randomized design (CRD), 4 treatments and 3 replications each. The treatments are P0 (conventional), P1 (2 cross-sectional units with an area of 1,087 cm2), P2 (4 section units with an area of 2,174 cm2), P3 (6 section units with an area of 3,261 cm2). Each treatment used the same filter, namely cotton, zeolite, pumice stone, and bio balls. The results of the research the highest absolute weight growth was obtained in the P3 treatment with an average value of 4.56 g and followed respectively P2 4.38 g, P2 3.03, P0 2.59 g. The highest absolute length growth rate was obtained in treatment P3 2.71 cm, P2 of 2.54 cm, P1 of 1.87 cm, and the lowest absolute length was found in treatment P0 of 1.62 cm. The highest feed conversion value was at P0 at 3.91, followed by P1 at 2.84, P2 at 2.06, and the lowest at P3 at 1.94. The highest survival value was P3 of 85.00, P2 r 83.33, P1 73.33 and the lowest was P0 of 55.00. The highest diversity coefficient value was obtained in treatment P0 of 17.58, followed respectively by treatment P1 of 16.05, P2 of 12.91 and the lowest coefficient of diversity found in treatment P3 of 12.69. The conclusion of this study is the use of different recirculation cross-sectional areas has a significant effect on absolute weight growth, absolute length growth, feed conversion ratio, survival, and water quality. The recirculation cross-sectional area in P3 treatment with a cross-sectional area of 3.261 cm2 gave good results for the survival of tilapia (O. niloticus).